Concrete Form of Legal Protection Against Buyers in Good Faith in The Buy and Buy of Land - I Made Ananda Dwirama Wiguna; I Nyoman Bagiastra (Westscience Press, 2024)
The principle of good faith receives less attention than other principles in civil law literature. This study aims to determine how buyers who buy and sell land in good faith are protected by the law. The normative legal research methods used in this study are utilized. One concrete form of legal protection for buyers who act in good faith is that if a judge decides that the buyer is a buyer who acts in good faith, he or she must also decide the status of the sale and purchase that has taken place. These are the findings of the research study that are the subject of the discussion. Is the sale and purchase object still the buyer's property, or does the sale and purchase status end and the buyer has to pay back the seller the money? Rather than having to file a lawsuit in court, which takes a considerable amount of time and cannot guarantee buyers' certainty of legal protection, this type of thing is certain to be sufficient to provide buyers in good faith with protection.